Exploring the Relationship Between Financial Competence and Entrepreneurial Ambitions in Digital Business Education - Kristian, Agus; Kusnadi; Supriyadi, Agung; Squire Sean, Rio; Husain, Abigail (APTISI Transactions on Management (ATM), 2024)
This research investigates the relationship between financial competence and entrepreneurial ambitions within the context of digital business education. The primary focus is on the impacts, challenges, and opportunities of integrating financial literacy into entrepreneurial training in digital business programs. We analyze significant changes in student aspirations and outcomes resulting from enhanced financial competence. This study identifies the crucial role of financial education as a driver of entrepreneurial success while exploring how educational strategies evolve to accommodate these new dynamics. This relationship's social, economic, and cultural impacts are also examined. The challenges educational institutions face in implementing these changes are presented alongside opportunities to enhance student innovation, efficiency, and sustainability. This research contributes to a deep understanding of the dynamic relationship between financial competence and entrepreneurial ambitions, detailing practical implications for educators and policymakers in the digital business education sector.